Effectiveness of a parent training program aiming to improve the psychological wellbeing and the family satisfaction: Parenting with a Smile (European Journal of Education and Psychology, 2020)
The purpose of this study was to design, implement and analyse the effectiveness of the parent training program Parenting with a smile, taking it as a structured role model in a psychoeducational intervention which aims to reduce anxiety, depression and stress symptoms by increasing the family satisfaction, the training in parenting skills and the change in attitude from parents with children aged between 0 and 12. A quasi-experimental study with a sample of 68 parents was carried out along with a pretest-posttest evaluation of the parents’ clinical symptoms in relation to anxiety, depression and stress by using the Abreviated Depression Anxiety Stress Scale [Escala Abreviada de Depresión, Ansiedad y Estrés (DASS-21)], of the family satisfaction following the Family Satisfaction by Adjectives Scale (FSAS) [Escala de Satisfacción Familiar por Adjetivos (ESFA)] and finally of the skills and cognitive dimensions related to parenting through the Questionnaire for the assessment of adopters, carers, tutors and mediators [Cuestionario para la Evaluación de Adoptantes, Cuidadores, Tutores y Mediadores (CUIDA)]. The reductions in clinical symptoms scores and the increase in family satisfaction and parenting skills, except for Altruism, shown in Wilcoxon test are significant.